Antiarrhythmic drug use in atrial fibrillation among different European countries – as determined by a physician survey - Espen Fengsrud; Carina Blomström-Lundqvist; A. John Camm; Andreas Goette; Peter R. Kowey; Jose L. Merino; Jonathan P. Piccini; Sanjeev Saksena; James A. Reiffel; Giuseppe Boriani (International Journal of Cardiology: Heart & Vasculature)
Background: There is limited knowledge of physicians’ antiarrhythmic drug (AAD) treatment practices for patients with atrial fibrillation and adherence to guidelines in European countries. Methods: An online survey (n = 321) of cardiologists, cardiac electrophysiologists and interventional electrophysiologists was conducted in Germany (DE; n = 83), Italy (IT; n = 95), Sweden (SE; n = 60) and the United Kingdom (UK; n = 83) including 96 questions on treatment practices. Results: ESC guidelines were the most important non-patient factor influencing treatment practice (55–72 %). However, while amiodarone was frequently (88–93 %) used in heart failure with reduced left ventricular ejection fraction, it was also a typical treatment choice for minimal/no-structural heart disease (SHD) (28 %), particularly in UK. Other deviations from guidelines were the use of class 1C drugs in coronary artery disease (CAD) and other SHD, and use of sotalol in left ventricular hypertrophy and renal impairment. In-hospital initiation of sotalol was low, with the exception of SE. Sotalol (16–41 %) and dronedarone use (10–54 %) in CAD varied among countries. For frequent, symptomatic paroxysmal AF, ablation was generally favoured, but AADs were preferred by 53 % in SE. In asymptomatic or subclinical AF, AADs were used by 41 % (range: 22–60 %), ablation by 11 % (range 2–18 %). In contrast to guidelines that prioritize safety, anticipated efficacy was more important (51 %) than safety (31 %) when selecting AADs. Conclusions: Despite recognizing the importance of guidelines, deviations in AAD use were common with the potential to compromise patient safety. These findings indicate the need for more educational support for optimal AAD selection in AF management.